The Application of Critical Discourse Analysis in Arabic Writing Course - Ari Khairurrijal Fahmi; Fitri Liza (UIN Sunan Gunung Djati Bandung, 2023)
Critical discourse analysis is a theory and a method used to dissect the relationship between language and society. This study examines how to apply the theory and methods of critical discourse analysis in learning to write Arabic. Learning to write Arabic is conical to academic writing, leading to the final project. The data in this study is the result of student writing, which is analyzed and studied through Rebecca Roger's critical discourse analysis theory. The results show that there is an interaction pattern of student writing formed through a peer review process as part of implementing the concept of critical discourse analysis.